Analisis Pengaruh Tipe Kondensor Terhadap Unjuk Kerja Mesin Pendingin Menggunakan Double Evaporator - Ardila Dwi Tresna; Boy Arief Fachri; Aris Zainul Muttaqin; M Nurkoyim Kustanto; Digdo Listyadi Setyawan; M Edoward Ramadhan (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
Separation condenser is one of the types of condenser equipped with gas and liquid separator. The previous research using separation condenser showed low output temperature of 1.3 K than baseline condenser. This study is to observe the effect of separation and baseline condenser to the performance of the refrigerator with a double evaporator and using LPG and R134A as a refrigerant. This research using a parallel circuit for separation condenser and baseline. The result showed that using R134A gives 0.16% higher value of COP. Meanwhile, using double evaporator with R134A as a refrigerant gives 69.5 % higher value of COP than single evaporator.